The role of respiration metabolism in dicyclohexylcarbodiimide and disodium succinate regulating the pulp breakdown occurrence of fresh longan (Dimocarpus longan Lour.) during storage - Yi Zheng; Yixiong Lin; Hongyi Wen; Yueying Sang; Mengshi Lin; Zhongqi Fan; Hui Wang; Yihui Chen; Yifen Lin; Hetong Lin (Food Chemistry: X)
Compared to control longan, on day 6, DCC-treated longan presented 18 %, 2 %, 15 %, 34 %, 21 %, 26 % and 10 % higher levels of pulp breakdown index, fruit respiration rate, PGI, SDH, NAD, NADH and QH2, respectively. Meanwhile, DCC-treated longan displayed 25 %, 5 %, 8 % and 12 % higher activities of respiratory terminal oxidases including CCO, AOX, PPO and AAO, respectively. However, DCC-treated longan presented 9 %, 27 %, 24 %, 25 % and 16 % lower levels of NADK, G-6-PDH + 6-PGDH, NADP, NADPH and Q, respectively. These data indicate that DCC-hastened longan pulp breakdown occurrence was owing to the diminished PPP, and the elevated EMP, TCA cycle and CCP, thereby leading to an increased respiration rate. However, DS treatment displayed contrary effects, indicating DS restrained longan pulp breakdown occurrence through diminishing the respiration metabolism and depressing the respiration rate of fresh longan.